Immunological microenvironment at the maternal-fetal interface. (June 2022) - Bian, Qiwu; Fu, Binqing
Abstract: The immune cells, especially innate immune cells (Natural Killer cells and Macrophages) residing at the maternal-fetal interface are playing critical roles during pregnancy. Here we discuss the immunological characteristic at the maternal-fetal interface during normal pregnancy. These key decidual immune cells are reshaped of their uterus-specific homeostatic functions within this uterus microenvironment. Through emphasizing the similarities and differences between decidua immune microenvironments with tumor or transplantation immune microenvironments, distinctive immune cell niche with activated, tolerant, proangiogenic and nurturing characteristic at the maternal interface is exhibited. Deeper understanding of the immunological microenvironment during pregnancy yield important insight not only into the pathogenesis of various human pregnancy complications, but also suggest ways to better manipulate these immune cells in cancer and transplant organs. Highlights: The immune cells, residing at the maternal-fetal interface constitute very special immunological interface during pregnancy. Similarities between NK cells in reproductive and tumor immune microenvironment reflect the plasticity of NK cells. The assumption that maternal immune system must be suppressed to make tolerance to the semi-allogeneic fetus is misleading. Maternal immune system during pregnancy should not be fully suppressed for normal pregnancy. The immune cells at the maternal interface show activated, tolerant, proangiogenic and nurturing characteristic.